Feeding Ecology with Prey Electivity and Growth Performance of Indigenous Asian Striped Dwarf Catfi sh, Mystus Vittatus (Bloch, 1794) in Low Saline Earthen Ponds of Indian Sundarbans - Asish Mondal; Deepta Chakravartty; Sufi a Zaman (Annals of Marine Science - Peertechz Publications, 2017)
Feeding ecology with prey preferences and fi sh growth of Mystus vittatus (Bloch, 1794) reared in low saline earthen polyculture ponds in Sundarbans were studied for 11th months during July, 2015 to June, 2016. Locally available wild collected mixed bagrid juveniles (4.3±0.14 cm, 1.20±0.99 g) including M. vittatus were stocked @ 1000 juveniles ha-1. No commercial feed or fertilizer was applied following common practice. According to the order of dominance the existing food items in water recorded were Chlorophyceae, Myxophyceae, Bacillariophyceae, Insect parts and larvae, Fish parts & larvae, Rotifers and Cladocera, Copepods and Crustacean larvae. Feeding intensity in terms of stomach fullness upgraded with increasing body weight of fish. The major food constituents in stomach were Copepods followed by Bacillariophyceae, Fish parts and larvae, Insect parts and larvae, unidentified organic matter, Chlorophyceae, Myxophyceae, Rotifers & Cladocera and Crustacean larvae. Prey electivity analysis indicated significantly active selection of Copepods (+0.53±0.05) and Bacillariophyceae (+0.31±0.06). Fish parts and larvae (+0.17±0.11), Insect parts (+0.06±0.07) and larvae and Crustacean larvae (0.02±0.17) were positively selected but not signifi cant. M. vittatus is an omnivorous fi sh and almost prefer zooplanktons. M. vittatus was attained average body weight 26.50±1.20g (13.6±0.19cm) with mean specific growth rate of 0.96±0.19 % day-1at harvest. Bagrid catfi sh performed isometric growth (W=0.012TL2.98) and good condition factor (1.14±0.046) indicating suffi cient of natural food materials in water. Health status of M. vittatus in low saline polyculture ponds is good.